A new endemic species of Hemidactylus (Squamata: Gekkonidae) from São Nicolau Island, Cabo Verde - Vasconcelos, Raquel; Köhler, Gunther; Geniez, Philippe; Crochet, Pierre-André (Zootaxa, 2020)
A new species of gecko of the genus Hemidactylus (Squamata: Gekkonidae) is described from São Nicolau Island, Cabo Verde Archipelago, and the Sal and Boavista island populations of Hemidactylus boavistensis (i.e., Hemidactylus boavistensis boavistensis comb. nov. and Hemidactylus boavistensis chevalieri comb. nov.) are recognized as subspecies. Hemidactylus nicolauensis sp. nov. is genetically distinct from H. bouvieri, to which it has previously been referred, and from all other closely related endemic Hemidactylus from Cabo Verde Islands in mitochondrial (12S & cyt b) and nuclear (RAG2, MC1R) markers. It is characterized morphologically by its distinct colouration and a diagnostically different arrangement of digital lamellae. With the description of this new species, São Nicolau is now known to harbour three single-island endemic gecko species, and the documented reptile diversity in Cabo Verde is raised to 23 endemic species. As a result of our taxonomic changes, existing conservation regulations should be updated and the conservation status of these taxa should be re-evaluated.